Antibacterial Effect of 96% Ethanol Extract of Papaya Seeds (Carica papaya L.) on the Growth of Staphylococcus aureus and Klebsiella pneumoniae causing Pneumonia - Fernanda Toriq Ainur Rochman; Eko Budi Koendhori; Dewi Ratna Sari; Manik Retno Wahyunitisari; Arifatun Nasicha (Majalah Biomorfologi, 2025)
Highlights Papaya seeds are a natural and traditionally used remedy in Indonesia, known for their safety and medicinal properties. The 96% ethanol extract of papaya seeds exhibits antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae.   ABSTRACT Background: Pneumonia is an infectious disease with the highest childhood mortality rate worldwide, commonly caused by Staphylococcus aureus and Klebsiella pneumoniae, which have developed resistance to antibacterial agents. Papaya seeds have traditionally been used in Indonesian medicine due to their bioactive compounds, which are expected to exhibit antibacterial properties. Objective: To analyze the antibacterial effect of 96% ethanol extract of papaya seeds against S. aureus and K. pneumoniae in vitro. Material and Method: This study employed a true experimental design with a posttest-only control group. Ethanol extracts of papaya seeds at concentrations of 10%, 30%, and 50% were tested using the well diffusion method. Erythromycin and chloramphenicol were used as positive controls, and 70% alcohol served as the negative control. Inhibition zone diameters were analyzed using SPSS version 29 with the non-parametric Kruskal-Wallis and Mann-Whitney tests. Results: The ethanol extract of papaya seeds inhibited the growth of S. aureus starting at a concentration of 10%, with the largest inhibition zone observed at 50%. Against K. pneumoniae, the extract demonstrated the lowest effective inhibitory concentration at 30%, which also produced the largest inhibition zone. However, the extract was less effective than the antibiotics used. Conclusion: The ethanol extract of papaya seeds exhibits antibacterial activity against both S. aureus and K. pneumoniae, with a more pronounced effect on S. aureus.